Методологічні підходи та методи дослідження конституційно-правового регулювання діяльності політичних партій - Кафарський, В.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследуется методологическая база правовой регламентации организации и деятельности политических партий, излагаются современные концепции и подходы к изучению соответствующего направления конституционного права, систематизируются методы соответствующего исследования. The analysis of methodological base which it is operated during researches of legal regulation of organization and activity of political parties is conducted in this work. An author conducted rich in content research of the historically folded and modern conceptions and approaches to the study of the proper direction of constitutional right. In the article approaches of authors are also realized to systematization and analysis of methods of the proper research.